2021
DOI: 10.3892/etm.2021.10640
|View full text |Cite
|
Sign up to set email alerts
|

Current research developments of patient‑derived tumour xenograft models (Review)

Abstract: Patient-derived tumor xenograft (PDTX) models are established by transferring patient tumors into immunodeficient mice. In these murine models, the characteristics of the primary tumor are retained, including the microenvironment of tumor cell growth and histopathology. Due to this, it has become the most reliable in vivo human cancer model. However, the success rates differ by type of tumor, site of transplantation and tumor aggressiveness. Subcutaneous transplantation is a standard method for PDTX, and subre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Further, several studies have shown high consistency between pre-clinical experiments using PDX models and results of clinical treatment. Therefore, the PDX models are useful in studying tumor pathogenesis and developing personalized treatment [ 16 , 17 , 33 ]. The tumor model generated by transplanting tumor cell lines into mice is different from the primary tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, several studies have shown high consistency between pre-clinical experiments using PDX models and results of clinical treatment. Therefore, the PDX models are useful in studying tumor pathogenesis and developing personalized treatment [ 16 , 17 , 33 ]. The tumor model generated by transplanting tumor cell lines into mice is different from the primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor model generated by transplanting tumor cell lines into mice is different from the primary tumor. Therefore, the drug dosage range tends to be different [ 33 ]. Therefore, the PDX model is a more reliable model for evaluating the anti-cancer effects of chemotherapeutic drugs [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The uses for these things are varied. Improved diagnosis and treatment of digestive illnesses may be achieved via research into the link between nutrient-rich foods, gut microbiota, and the organisms presently serving as hosts [229][230][231][232]. Patient-derived models are now widely available, allowing their usage by researchers from all across the world.…”
Section: Future Concepts and Opinions Examinedmentioning
confidence: 99%
“…In the first series, lymphoma cell implantation was performed via the s.c. route derived from seven patients [40]. After s.c. implantation, two out of three SCNSL samples engrafted at the site of implantation but only one out of four PCNSL biopsies engrafted.…”
Section: Establishment Of Primary and Secondary Cns Lymphoma Pdx Modelsmentioning
confidence: 99%